Implementation of the population-based cancer registry in the city of Mérida, Mexico: process and early results - Yelda A Leal; Nancy Reynoso-Noverón; Luis Fernando Aguilar-Castillejos; Abelardo Meneses-García; Alejandro Mohar; Marion Piñeros (Instituto Nacional de Salud Pública, 2019)
Objective. To briefly describe the process of establishment and preliminary results of the Mérida Population-based Cancer Registry (Mérida-PBCR) Materials and methods. Mérida-PBCR started in 2016 as a research project in the IMSS, with a gradual increase in its information sources. It covers a population of 908 536 inhabitants. Data collection is active and passive, international standards are used; CanReg5 software enables data entry, storage and analysis. Results. Current data include 71.5% of sources. For the period 2015- 2016, a total of 2 623 new cancer cases were registered, the majority of these (60.1%) among females. 81.5% of the cases had morphological verification. Prostate (17.4%), colorectal (8.5%) and stomach (8.1%) cancers were the most common among males, and breast (31.6%), cervix (12%) and corpus uteri (7.6%) cancers, the most common among females. Age-adjusted cancer incidence rates (per 100 000) for all sites combined were 114.9 among males and 145.1 among females. Conclusion. The implementation of the Mérida-PBCR has followed particular parameters, with important efforts to include new information sources. Although the data are still preliminary and must be interpreted with great caution, the main cancers follow a similar pattern to that of the national and regional estimates.